2015
DOI: 10.1111/fme.12114
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in life history traits of three small fishes in streams of south‐eastern Brazil

Abstract: Each species has a reproductive strategy that is adapted to the intensity and predictability of spatial and temporal variations in local environmental conditions. This study sets out to evaluate the temporal and spatial variations in some life history traits, including maturation time and length at first maturity, of three small fish species from streams of south‐eastern Brazil. Environmental factors and fishes were sampled in streams across four sub‐basins during twelve months and were measured for both trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Based on the L50, the total length ranged from 2.05 cm to 4.2 cm for individuals of Astyanax sp. congeneric species, from 4.1 cm to 4.5 cm for P. stramineus, from 2.79 cm to 3.75 cm to P. argentea and higher than 3.2 cm for S. hetero don (Gomiero et al, 2007;Castro et al, 2010;Gonçalves et al, 2011;Lourenço et al, 2015).…”
Section: Suitability Curves and Regression Models For Fish Densitymentioning
confidence: 89%
“…Based on the L50, the total length ranged from 2.05 cm to 4.2 cm for individuals of Astyanax sp. congeneric species, from 4.1 cm to 4.5 cm for P. stramineus, from 2.79 cm to 3.75 cm to P. argentea and higher than 3.2 cm for S. hetero don (Gomiero et al, 2007;Castro et al, 2010;Gonçalves et al, 2011;Lourenço et al, 2015).…”
Section: Suitability Curves and Regression Models For Fish Densitymentioning
confidence: 89%
“…This might be due to the warmwater environment in the SA, which consists of seawater with high temperature and salinity, whereas the water system in NA is coastal water with low salinity and high‐nutrient salt (Beardsley et al 1985; Chern and Wang 1990; Ichikawa and Chaen 2000). The water temperature difference is a known driver of geographical variation in fish maturation rates (Farley et al 2014; Lourenco et al 2015; Wang et al 2008), as ectotherms tend to grow faster and mature earlier at warmer temperatures than at cooler temperatures (Angilletta et al 2004; Brunel and Dickey‐Collas 2010; Matta et al 2016). Our results also suggested that SST significantly affected the maturity schedules in female Hairtail (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of young fish in the lift may be due to the attraction of this waterfall at its entrance or these animals may be carrying out a migration of the regional colonization to the dam's upstream and not a reproductive migration. Increasing regional temperature and rainfall during the study period may have influenced the gonads maturation, as these factors are environmental variables that influence individuals, so that conditions in the spawning season are conducive to offspring survival and growth (Lourenço et al, 2015, Vazzoler, 1996.…”
Section: Discussionmentioning
confidence: 99%